The Impact of Social Media (Facebook and YouTube) on Vocabulary Acquisition of ESL Learners - Afshan Abbas; Rehana Gulzar; Zahoor Hussain (Journal of Communication and Cultural Trends, 2019)
This research paper studies the impact of social media, specifically, Facebook and YouTube, on vocabulary acquisition of ESL learners. Using data collected from 30 students studying at the Department of English, IIUI, Islamabad and online responses from teachers with PhD in English, we strove to find out how learners are assisted by social media in vocabulary acquisition. It was discovered through the responses that the majority of teachers and students believe that vocabulary acquisition is improved through social media as it enhances the level of interest of students in second language learning. Overall, this study allows us to analyze the differences in the learning habits of ESL (English as Second Language) learners in a typical classroom environment using the new electronic media which is social media.